Shared-appreciation mortgages and uninsurable idiosyncratic shocks - Richard Cóndor (Banco de México, 2020)
Shared-appreciation mortgage (SAM) contracts, which display payments indexed to a local house price, have been proposed as an alternative to alleviate the costs of recessions. Using a heterogeneous agent model with two types of agents (Borrowers and Savers), uninsurable idiosyncratic income risk, and calibrated to the US, this paper studies the effects, on both macroeconomic variables and welfare, of introducing such contracts. I find that equilibrium default rates, house price volatility, and welfare losses of both Borrowers and Savers following an unexpected negative shock on aggregate income, are smaller. Also, while this policy benefits Savers, only Borrowers with moderate/low mortgage and housing wealth levels are better-off (61% of Borrowers under the main calibration). Finally, if Borrowers are less patient, the fraction that benefits may never be above 50%.
Keywords: G00; C61; E44; 330; Mortgage design; Heterogeneous agents; Housing policy